The decomposition of information and communication technology products trading: A case study of China - Jinghui Duan; Yinuo Liu (Economies, 2022)
Technology is recognised as one of the most important factors in world economic development, particularly contributing to the trade growth of information and communications technology (ICT) products. The decomposition of export growth has been a popular way to analyse how trade has been influenced since 2000. However, there is little investigation regarding the structure of ICT product trading of China, which is the de facto largest trader of ICT goods export and import. This paper contributes to the existing methods with a non-parametric model. The coefficient estimates which functions of their factors represent a dynamic analysis of the factors' influence on decomposed trade growth. The empirical study shows that China's strategy tends to be conservative, as the growth of trade to developed countries mostly came from the volume increase of existing trade lines instead of the increase of trade varieties. Suggestions include that the trade growth could benefit from resource reallocation in ICT industries and the procedure simplification of exporting ICT products. This paper also provides empirical evidence that the Belt and Road Initiative (BRI) increased the trading volume and frequency by completing the transportation chain and decreasing the variable trade costs. Furthermore, suggestions are provided on improving the impact on the globalisation of ICT.
Keywords: 330; ICT products; policy; strategy; the intensive and extensive margins; trade growth